Value and semantic orientation of a Gothic personality in Scotus’s axioms of beatitudo aspiration - Oleg Turenko (Cхід, 2019)
A common conviction of Modernism about personality’s absence in the High Middle Ages is criticized in the issue. From Duns Scotus’s axioms, scholastic directives about necessary aspiration of bliss which characterizes a true Christian believer, the author has proved that scholastic doctrines of the period are aimed at a process of moral, reflective and responsible person formation whose deliberately remains an unchanged balance between individual and collective values. The hermeneutical, phenomenological, logical and critical methods are used to reveal social and mental senses of ethical and religious category of bliss in Duns Scotus’s doctrine and axiological mainstreams’ determination of personality development in the High Middle Ages. The Scotus’s interpretation of bliss aspiration is proved to state a concept of active individual development and emphasizes a process of personality formation, encourages a man to self-control and the inner world harmonization according to Christian canonical values and ideas of believers from various communities - families, corporations, states, which create the integral “Christian community” (corpus Christianorum). A béatitudo aspiration is a hierarchical guideline and a mean of active spiritual and moral motion beginning, as well as it is one of the will’s direction facilities toward an ideal object. The bliss aspiration provides an opportunity to realize abilities of will-love, to overcome depravity interim ethics, by eliminating its contingent notion, and after having known a natural sphere of bliss, wishing happiness. Scholar considers béatitudo a bail of Love and God’s plan in an ordinary human life, as a certain man’s gift that facilitates to reach finis ultimus. Despite a level of depravity a man should personally harmonize two spheres of bliss, in particular private and universal spheres. Nevertheless, due to a natural law human nature primarily desires happiness in a private sphere, and then bliss in a universal sphere that will be reached by a posteriori acts of will and an equal dilemma solution. A philosophic interpretation of a bliss category is created for the first time. The perspectives of further study will allow contemporaries an additional opportunity to understand the anthropological transition from traditional way of thinking to rational and individual one and to determine the internal filling of medieval human’s spiritual world, that are the mental milestones in a process of a European personality formation.